A novel scheme for modelling and analysis of spot-welded shell structures using interface shell elements. (15th October 2020) - Ho-Nguyen-Tan, Thuan; Kim, Hyun-Gyu
Highlights: Spider-web meshes representing spot welds can be easily placed in a global mesh. High-quality meshes around spot welds are generated without any global remeshing. Interface shell elements are created by cutting a global mesh with spider-web meshes. Locking phenomena in interface shell elements are alleviated using assumed strains. Abstract: In this study, a novel scheme for modelling and analysis of spot-welded shell structures is presented by placing local spider-web shell meshes representing the weld nugget region in a global shell mesh. Interface shell elements are employed for trimmed shell elements with arbitrary number of nodes created by cutting a global shell mesh with the boundaries of local spider-web shell meshes. Transverse shear and membrane locking phenomena in interface shell elements are effectively alleviated by introducing assumed natural strain fields. Conventional elastic beam elements with six degrees of freedom are used to connect the center nodes of local spider-web shell meshes. The present method can construct high-quality shell meshes around spot welds without any global remeshing, which makes it very efficient and effective for the analysis of spot-welded shell structures.